The Rebirth of People and Earth: COVID-19 as a â€œHealerâ€ in Kitty Oâ€™Mearaâ€™s Picturebook and the People Stayed Home - Saaffan, Mai; Mahmoud, Radwa (Journal of Ecohumanism, 2024)
Kitty Oâ€™Mearaâ€™s picturebook And the People Stayed Home (2020) presents COVID-19 as a potential â€œhealerâ€ that fosters the rebirth of people and earth. Oâ€™Mearaâ€™s poem, â€œIn the Time of Pandemic,â€ conveys a message of hope, resilience, and reflection in the face of the pandemic. When accompanied by the illustrations of Stefano Di Cristofaro and Paul Pereda, the poem takes on a new dimension as a picturebook. The article examines Oâ€™Mearaâ€™s picturebook, exploring how the visual elements enhance the emotional impact and deepen the interpretation of the text. Oâ€™Mearaâ€™s picturebook is examined through the lens of both ecocriticism and picturebook theory. Leaning on both theories, the article reveals deeper meanings and implications regarding the relationship between the pandemic, the environment, and human society. By analyzing the visual and textual elements of the picturebook, the article uncovers the ways in which these illustrations highlight the interconnections between humanity and the natural world.